The problem of determining biological age in the assessment of physical development and prenosologicaldiagnosis of constitutional diseases - Ажиппо Олександр Юрійович, (Oleksandr Aghyppo); Пугач Ярославна Ігорівна, (Yaroslavna Puhach); Жерновнікова Яна Вікторівна, (Yana Zhernovnikova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: establish the basic framework for the process of physical development and causes of the individual features of its occurrence. Material and Methods: analysis and synthesis of scientific literature on this problem, and anthropometric studies of the observed population. Results: the process of physical development is presented as two interdependent components - the body weight and its shaping, which allowed to present the structure of the variability of body shaping. Conclusion: the features of the structure formative mass in its accumulation to a certain extent implemented in the organogenesis of morphological and functional entities, that reflecting their maturation. Norm of interdependence of these relations defines the individual characteristics of the physical development of the organism.